Monitoring regulatory T cells as a prognostic marker in lung transplantation - Khan, Mohammad Afzal; Lau, Christine L.; Krupnick, Alexander Sasha (Frontiers in Immunology, 2023)
Lung transplantation is the major surgical procedure, which restores normal lung functioning and provides years of life for patients suffering from major lung diseases. Lung transplant recipients are at high risk of primary graft dysfunction, and chronic lung allograft dysfunction (CLAD) in the form of bronchiolitis obliterative syndrome (BOS). Regulatory T cell (Treg) suppresses effector cells and clinical studies have demonstrated that Treg levels are altered in transplanted lung during BOS progression as compared to normal lung. Here, we discuss levels of Tregs/FOXP3 gene expression as a crucial prognostic biomarker of lung functions during CLAD progression in clinical lung transplant recipients. The review will also discuss Treg mediated immune tolerance, tissue repair, and therapeutic strategies for achieving in-vivo Treg expansion, which will be a potential therapeutic option to reduce inflammation-mediated graft injuries, taper the toxic side effects of ongoing immunosuppressants, and improve lung transplant survival rates.